A semantic approach in perception for packaging in the SME's food industries in Malaysia: a case study of Malaysia food product branding in United Kingdom - Zainal Abidin, Sazrinee; Raja Ahmad Effendi, Raja Ahmad Azmeer; Ibrahim, Rahinah; Idris, Muhammad Zaffwan (Elsevier, 2014)
Purpose – This paper is to evaluate the perception for the food packaging and branding for Malaysia SME's food industries in United Kingdom. This study uses literature survey, questionnaire, semantic evaluation and observations. Additionally, this research would also show the evidences of semantic selection and global strategies by the brand owner closely related to the consumers. Attributes for a successful brand, packaging and marketing are available for references for any SMEs before going global. The innovation and creativity tackling all the problems on branding, packaging design and global market have make it more strategic and direct in creating solutions for internationalization and standardization.